KECEMASAN MEMBACA DALAM PERSPEKTIF NEUROSCIENCE - Hidayat, Arip; musaljon, Musaljon (Fascho: Kajian Pendidikan dan Sosial Kemasyarakatan, 2019)
This study aims to show the role of emotions in encouraging effective learning. The affective domain is always considered less significant in the learning process than the cognitive domain. The reader of this article is expected to understand how the role of emotions in the learning process, using cognitive psychology theory and neuroscience  analysis from this study. Next, examine the effect of the affective domain on learning in symbol interpretation. This paper concludes with analysis of reading anxiety and suggestions in reading exercises.